First report of Yokenella regensburgei isolated from external auditory canal after diving in valley - Gina Na; Je Eun Song; Jeonghyun Chang (Clinical Case Reports, 2021)
Abstract Yokenella regensburgei is a Gram‐negative, oxidase‐negative motile rod which is rarely isolated from human caused a few opportunistic infections in immunocompromised patients so far. We report the first case of otitis media combined with externa caused by Y. regensburgei in an immunocompetent patient. A 56‐year‐old male patient visited the outpatient clinic of the Otolaryngology Department due to otorrhea of the right ear started after diving in mountain valley in Korea 3 days ago. He was immunocompetent adult and clinical examination revealed swelling and debris accumulation in the right external auditory canal with an intact, erythematous tympanic membrane, and clear, odorless otorrhea. Microbiological culture of otorrhea revealed Y. regensburgei by matrix‐assisted laser desorption/ionization time‐of‐flight and PCR‐based 16S rRNA gene sequencing. His otorrhea persisted, and a pinpoint perforation occurred in the inferior anterior portion of the tympanic membrane. 50% acetic acid irrigation and 500 mg of oral ciprofloxacin were prescribed, and his infection was cured after 4 weeks. This is the first case of otitis media combined with externa caused by Yokenella regensburgei in an immunocompetent patient. Given that Yokenella species infections are rare, especially in immunocompetent patients, this case highlights the importance of history taking and communication between clinicians and laboratory physicians. Molecular identification methods assist in identifying rare pathogens.